Countering Violent Extremism in Trinidad and Tobago: An Evaluation - Aldrich, Daniel P. (Terrorism and political violence, 2023)
This paper investigates the history of violent extremism and evaluates the status of countering violent extremism (CVE) policies in Trinidad and Tobago, focusing on government, international partners, and NGO programming. Through more than twenty extended interviews with grassroots organizations, politicians, and members of the security administration alongside an exploration of budgetary and personnel data, we seek to illuminate major challenges to official policies and actual, on the ground practices. on the ground practices. Our evaluation of extremist manifestation, government rebalancing, and cross sectoral alignment shows that while authorities in Trinidad and Tobago have recognized the power of non-state actor centered, bottom-up policies in reducing support for terrorism, most visible operations continue to rely on top down, state centric ones. This paper brings with it concrete recommendations for law enforcement, community builders, and residents alike.